Literasi Sains melalui Pendekatan Saintifik pada Pembelajaran IPA SD/MI di Abad 21 - Tuti Rezeki Awaliyah Siregar; Wahyu Iskandar; Muhammad Agung Rokhimawan (MODELING: Jurnal Program Studi PGMI, 2020)
Science literacy is developing very rapidly and is entrenched in this era '21st century'. In reality the 21st century focuses on scientific-based learning. This study aims to find out how scientific literacy through scientific approaches to learning science SD / MI in the 21st century. The method used in this research is library research or library studies that rely on bibliographic sources from various literary bases both books and scientific articles. then objectively packaged in the reading of the data as well as the sharpness of the analysis of the related discussion. The results of this study that scientific literacy through a scientific approach is guaranteed to be able to deliver students in the ability to have scientific processes, scientific attitudes and be able to communicate a problem scientifically. Science literacy is also very much needed in learning SD/MI science in this '21st century', bearing in mind that the Indonesian nation is currently 'underdeveloped' in the scientific and literacy aspects when compared to developed countries.